Compliance With Infection Control Guidelines in the Operating Rooms - Parisa Mohammad Ali Nejad; Saghi Mousavi; Atefe Ghanbari Khaneghah; Zahra Atrkar Roushan; Neda Feyz Mangouhi (Journal of Holistic Nursing and Midwifery)
Introduction: Compliance with the safety standards in the operating rooms, as one of the most complex work environments in the health care systems, is very important. One of the safety measures is the infection control standard. Objective: This study aimed to investigate compliance with infection control standards in the operating rooms of teaching hospitals in Rasht City, Iran. Materials and Methods: This research was an analytical cross-sectional study. A researcher-made checklist was used to examine physical structure, equipment and facilities, and the personnel performance of 11 operating rooms in six teaching hospitals affiliated to the Guilan University of Medical Sciences in Rasht City with respect to infection control standards. The obtained data were analyzed using descriptive statistics and Fisher test. Results: The rate of compliance with infection control standards associated with the physical structure of the operating room was 72.7% and for equipment and facilities as well as personnel performance was 59.1%. There was no statistically significant relationship between compliance with infection control standards in the area of personnel performance, work shift, or the number of elective and emergency operations. Conclusion: The compliance of physical structure, equipment and facilities, and the personnel performance of the operating rooms with infection control standards were at moderate level. Thus, the operating rooms in our hospitals may need monitoring and examination.